2009
DOI: 10.1158/0008-5472.can-08-3218
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Comparison of Allelic Imbalance between Noninvasive and Invasive Small-Sized Lung Adenocarcinomas

Abstract: Seventy-two small-sized (V2 cm in diameter) lung adenocarcinomas consisting of 15 noninvasive and 57 invasive tumors were subjected to whole genome allelic imbalance (AI) scanning and mutational analysis of the EGFR, KRAS, and TP53 genes to elucidate genetic pathways of early-stage lung adenocarcinomas. The chromosome 13q13 region showed the most frequent AI (58%) and was affected at similar frequencies between noninvasive and invasive tumors (53% and 60%, respectively), as EGFR and KRAS mutations were. The nu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 30 publications
2
32
1
Order By: Relevance
“…In 92 cases of small-sized lung ADCs, cancer cells were obtained by laser capture microdissection using the PixCell Laser Capture Microdissection System (Arcturus Engineering) as previously described (17), and noncancerous lung tissues were obtained from regions greater than 5 cm from tumors with macroscopically normal morphology in the resected lobes of the lungs. Sixty-five cases were subjected to 10-K singlenucleotide polymorphism (SNP) array analysis as reported previously (12), and 60 cases were subjected to real-time genomic PCR (RT-G-PCR) analysis. Thirtythree of the 92 cases were subjected to both analyses.…”
Section: Patients and Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 92 cases of small-sized lung ADCs, cancer cells were obtained by laser capture microdissection using the PixCell Laser Capture Microdissection System (Arcturus Engineering) as previously described (17), and noncancerous lung tissues were obtained from regions greater than 5 cm from tumors with macroscopically normal morphology in the resected lobes of the lungs. Sixty-five cases were subjected to 10-K singlenucleotide polymorphism (SNP) array analysis as reported previously (12), and 60 cases were subjected to real-time genomic PCR (RT-G-PCR) analysis. Thirtythree of the 92 cases were subjected to both analyses.…”
Section: Patients and Tissuesmentioning
confidence: 99%
“…Type A localized bronchioloalveolar carcinoma (LBAC), and type B LBAC with foci of alveolar structural collapse, are noninvasive tumors, while type C, LBAC with foci of active fibroblastic proliferation, and type D, poorly differentiated ADC, are invasive tumors. To efficiently detect the association of copy number alterations with prognosis, all type C cases with relapse and random type C cases without relapse were selected for this cohort; therefore, the relapse-free survival rate of type C cases selected was considerably lower than that of all type C cases, and the population of advanced stages (>IA) in type C cases was higher than that in all type C cases, as previously described (12). In 162 cases of stage I lung ADCs, the cancer cells and the corresponding noncancerous cells were macrodissected.…”
Section: Patients and Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…TP53 was identified to mutate in lung carcinoma (Le Calvez et al, 2005). Furthermore, the frequency of TP53 mutations in invasive tumors was significantly higher than those in noninvasive ones (Nakanishi et al, 2009). SP3 belongs to a family of 16 different transcription factors containing a highly conserved zinc finger DNA-binding domain (Philipsen and Suske, 1999).…”
Section: 1477 Bioinformatics Analysis Reveals Connection Of Lung Sccmentioning
confidence: 99%
“…We found that KRas mutations occurred significantly more frequently in patients who had a tumor >31 mm in diameter than in patients who had a tumor ≤30 mm. The KRas mutation is thought to be an early event that plays a role in tumor initiation (34,35). Woo et al (36) reported that the KRas mutation and a tumor size >30 mm were independent prognostic factors in stage I lung adenocarcinoma (KRas mutation; Hr 4.51, 95% cI 1.68-12.06, p=0.003, tumor size >30 mm; Hr 4.55, 95% cI 1.61-12.82, p=0.004, respectively).…”
Section: Egfr Genotype Kras Genotype --------------------------------mentioning
confidence: 99%